Petrogenesis of the Early-Triassic quartz-monzodiorite dykes from Central Jebilet (Moroccan Meseta): Trace element and Nd-Sr isotope constraints on magma sources, and inferences on their geodynamic context. (January 2019) - Bouloton, Jacky; Gasquet, Dominique; Pin, Christian
Abstract: A dyke swarm composed of hypabyssal rocks of intermediate composition cross-cuts Variscan granites and Palaeozoic metasedimentary country-rocks of the Jebilet range. Based on K-Ar isotope dating on kaersutite phenocrysts, these dykes are Early Triassic in age (ca. 240 ± 10 Ma). Due to more or less pervasive alteration, the primary mineralogical assemblages are often difficult to unravel. Plagioclase and amphibole are ubiquitous, but the extent of biotite, for instance, is subject to discussion. Two distinctive types of rocks are clearly present according to their mineralogical composition: most samples are characterized by a light-brown to greenish hornblende, while some samples are characterized by the presence of kaersutite, suggestive of an alkaline affinity. Incompatible trace element data, restricted to those elements which are considered to be relatively immobile during alteration processes, allow two groups of samples to be distinguished. The largest one displays distinctive negative Ti and Nb anomalies similar to those typical for magmas extracted from mantle sources, which interacted with hydrous fluids and silicate melts, and were thus enriched in Th and LREE relative to the HFSE. However, Nd and Sr data preclude late stage crustal contamination as a suitable explanation of these features in all but the most evolved samples. The LREE enrichment combined with relatively radiogenic Nd isotope signatures are interpreted to reflect the characteristics of source materials, which evolved in a rather primitive, ensimatic setting. The second group comprises only three samples but is of major interest as it does not show any clear Nb negative anomaly and its Th/Nb systematics suggests that crustal components were not involved in their genesis. This group is interpreted as having been produced through partial melting of mantle sources which did not suffer hydrous metasomatism nor recycling of old crustal components, but were enriched in a within-plate setting by low-degree mantle melts. Based on these data, the following tentative geological scenario is proposed. Lithospheric stretching and decompression would have triggered partial melting at relatively deep level of the lithosphere, and produced magmas with within-plate, alkaline-affinities. The ascent of these hot mantle melts would have triggered partial melting of fertile, hydrated domains of Late Proterozoic age present in the overlying mantle and/or lower crust, thereby generating the volumetrically predominant group of samples with « calc-alkaline » geochemical features, namely Nb and Ti negative anomalies. The two types of magmas likely interacted to produce hybrid liquids with variably deep Nb anomalies but broadly constant εNd values, as a result of the weak difference of their isotope signatures. These magmas are much younger (ca. 240 ± 10 Ma) than the last Variscan granites dated at ca. 300 Ma. On the other hand, they largely predate the tholeiitic continental flood basalts of the Central Atlantic Magmatic Province (CAMP) emplaced at ca. 200 Ma, and were thus emplaced amidst the 100 Ma time span between the end of the Variscan orogeny and the lithospheric break-up that led to the formation of the Atlantic Ocean. Therefore, the Jebilet dykes neither represent the ultimate manifestation of the Variscan orogeny nor a premise of the Atlantic opening. Instead, they document a particular event within a protracted intra-continental rifting history spanning the whole Permo-Triassic period. In general terms, this distensive event might be viewed as a local consequence of the dextral mega-shear which separated Europe from North Africa in Late Palaeozoic times. In this scope, the studied dykes could be described as a set of tension gashes, resulting from a local change in stress regime. Their formation was accompanied by a small pulse of intraplate magmatism, possibly because favorable fertile materials occurred locally at depth. At a larger scale, the whole dyke swarm cross-cutting the Variscan basement in Morocco is indicative of an aborted rifting event, largely predating the successful break-up of Pangea and the early opening of the Central Atlantic Ocean. Highlights: Most samples display negative Nb and Ti anomalies suggestive of a crustal imprint. Magmas present features reminiscent of both calc-alkaline and alkaline affinities. Th/Nb systematics suggests the absence of any crustal component input for 3 samples. Isotopic features of the rocks reflect characteristics inherited from diverse sources. These dykes document an Early Triassic (ca. 240 ± 10 Ma) specific distensive event.